Oxytocin Massage, Breast Milk Production, and Comfort in Post Partum P0A1 Mothers with Spontaneous Delivery: A Case Study in the Delima Room of RSUD Waled - Vivy Zakiyah; Raeisya Azriliyani; Julia Afriani; Yulia Rahmawati; Muadi Muadi (Al Makki Health Informatics Journal, 2024)
All pregnant women have the potential to experience complications during pregnancy and the postpartum period. To prevent complications such as bleeding and infection in the postpartum period, comprehensive nursing care is essential, including counseling on postpartum care. This counseling aims to meet the mother's need for knowledge and skills related to self-care, newborn care, family adaptation, and health recovery.  This study aims to describe the implementation of nursing care in postpartum mothers through the nursing process approach. A case study design was used on primiparous postpartum mothers with spontaneous delivery in the Delima room, Waled Hospital, Cirebon Regency. The research was conducted on February 12, 2024.  The results showed that breast milk production can be accelerated by nonpharmacological measures such as oxytocin massage, which involves massaging the area around the back (vertebrae pars thoracica) to stimulate the release of breast milk. The mother reported feeling satisfied, happy, and confident in her ability to provide breast milk to her baby. Although the problem of ineffective breastfeeding related to inadequate milk supply was not fully resolved, patients reported feeling comfortable after oxytocin massage. The implication of the study suggests that oxytocin massage can be an effective intervention in accelerating milk release and improving the well-being of postpartum mothers. Appropriate counseling and nursing care are crucial in helping postpartum mothers overcome challenges and improve the quality of self-care and newborn care.